Some reversed degree-based topological indices for graphene. (3rd October 2019) - Kwun, Young Chel; Virk, Abaid Ur Rehman; Rafaqat, Muhammad; Rehman, Mutee Ur; Nazeer, Waqas
Abstract: Topological indices are numerical values that correlate the chemical structures with physical properties. In this article, we will discuss some new reverse degree based topological indices namely reverse first zagreb index, reverse second Zagreb index, reverse third Zagreb index, reverse Atom-bond connectivity index and reverse Geometric-arithmetic inde